Social media, a media of personalization? : a content analysis of the 2017 Icelandic parliamentary elections - Baldur Sverrisson 1996- (2018)
Social media are as popular of a tool in campaign communication in Iceland as it is in most of the Western world. Research from around the world suggests that social media is one of the causes of increased personalization of politics in recent years. There has not, however, not been any research into this personalization in Iceland, making this research is the first attempt. This paper includes results from interviews with party officials as well as a content analysis of social media posts on Facebook, Snapchat and Twitter by the top two candidates from each party that ran in all constituencies. The analysis divided the posts into three categories: two of them being personal communication ( non-political personal and political personal) and one non-personal (non-personal political). This research explores whether social media is a tool for dominantly personalized political communication in Iceland. The research question was: Are social media a tool for dominantly personalized tool in Icelandic political communication? The results mostly focus on Facebook due to its importance in Iceland in comparison to the others, which was suggested both by the interviews and the results of the content analysis where it was dominant in the number of candidates using it and the number of posts. To see if the communication was dominantly personal the personalized categories, the candidates personal politics and non-political personal communication, were combined and put up against the non personal one, political non-personal. The data was then analysed in the light of 8 variables: gender, constituency, leadership, party, if they got elected or not, if they are from an old or a new party, how active candidates were, and if the posts came from a party account or a candidate account. The results suggested that was that social media communication by candidates is dominantly personal Vægi samfélagsmiðla í kosningabaráttu hefur aukist síðustu ár á Íslandi líkt og í stærstum hluta hins vestræna heims. Rannsóknir benda til þess að ...